DAMPAK SOSIAL EKONOMI KERUSAKAN HUTAN CYCLOOPS PADA MASYARAKAT DI DISTRIK SENTANI, KABUPATEN JAYAPURA - HALOMOAN, HUTAJULU (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2010)
Area size of degraded land in Cycloops was 9.374 ha, from the total area size of 22.500 ha. The objectives of this research were describing forest damage in Cycloops, estimating economic impact from Cycloops forest damage, and formulating action for overcoming Cycloops forest damage. This research was conducted by the following approach es: change of productivity, cost of medical remedy, qualitative description, and transfer benefit. The research results show whereas the impact of flood/landslides in Cycloops has reduced farming productivity with the loss value of Rp 35,725,262,500, decreased public health Rp 152,325,000, the damage to public facilities and infrastructure Rp 51,778,194,000. The total value of economic loss as a result of floods/ landslides in Cycloops was Rp 88,401,754,100. Value of WTP community Rp 24,513,878,150. The results of AHP show that stakeholder LMA and the Community an important role in controlling the forest damage in Cycloops with value 0.30. A right approach of policies in the form of Preserved and Environmentally-Friendly Forest had the value of 0.66. The ratio value of consistency was 0.04. An alternative policy for the development of Cycloops region is an Empowerment of Forest Community with the value of 0.34, which means that the local community must be empowered.
Keywords: social economic impact, forest damage, community, CAPC